The NEALS primary lateral sclerosis registry. (2nd November 2020) - Paganoni, Sabrina; De Marchi, Fabiola; Chan, James; Thrower, Sara K.; Staff, Nathan P.; Datta, Neil; Kisanuki, Yaz Y.; Drory, Vivian; Fournier, Christina; Pioro, Erik P.; Goutman, Stephen A.; Atassi, Nazem; et al.
Abstract: Background and objective: Primary lateral sclerosis (PLS) is a neurodegenerative disease characterized by progressive upper motor neuron dysfunction. Because PLS patients represent only 1 to 4% of patients with adult motor neuron diseases, there is limited information about the disease's natural history. The objective of this study was to establish a large multicenter retrospective longitudinal registry of PLS patients seen at Northeast ALS Consortium (NEALS) sites to better characterize the natural progression of PLS. Methods: Clinical characteristics, electrophysiological findings, laboratory values, disease-related symptoms, and medications for symptom management were collected from PLS patients seen between 2000 and 2015. Results: The NEALS registry included data from 250 PLS patients. Median follow-up time was 3 years. The mean rate of functional decline measured by ALSFRS-R total score was −1.6 points/year (SE:0.24, n = 124); the mean annual decline in vital capacity was −3%/year (SE:0.55, n = 126). During the observational period, 18 patients died, 17 patients had a feeding tube placed and 7 required permanent assistive ventilation. Conclusions: The NEALS PLS Registry represents the largest available aggregation of longitudinal clinical data from PLS patients and provides a description of expected natural disease progression. Data from the registry will be available to the PLS community and can be leveraged to plan future clinical trials in this rare disease.